Respostas
respondido por:
2
x²-5x+6=0
Usando a fórmula:
x=-b²+/-√b²-4ac ÷ 2a
Sendo a=1 b=-5 e c=6
Substituindo os valores:
x= 5+/-√ 5²- (4×1×6) ÷ (2×1)
x= 5+/-√25-24÷2
x=5+/-1 ÷2
x1= 5+1÷2
x1= 3
x2= 5-1÷2
x2=2
Usando a fórmula:
x=-b²+/-√b²-4ac ÷ 2a
Sendo a=1 b=-5 e c=6
Substituindo os valores:
x= 5+/-√ 5²- (4×1×6) ÷ (2×1)
x= 5+/-√25-24÷2
x=5+/-1 ÷2
x1= 5+1÷2
x1= 3
x2= 5-1÷2
x2=2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás